How is community based 'out-of-hours' care provided to patients with advanced illness near the end of life: A systematic review of care provision. (March 2023) - Firth, Alice M; Lin, Cheng-Pei; Yi, Deok Hee; Goodrich, Joanna; Gaczkowska, Inez; Waite, Frances; Harding, Richard; Murtagh, Fliss EM; Evans, Catherine J
Background: Deaths in the community are increasing. However, community palliative care out-of-hours is variable. We lack detailed understanding of how care is provided out-of-hours and the associated outcomes. Aim: To review systematically the components, outcomes and economic evaluation of community-based 'out-of-hours' care for patients near the end of life and their families. Design: Mixed method systematic narrative review. Narrative synthesis, development and application of a typology to categorise out-of-hours provision. Qualitative data were synthesised thematically and integrated at the level of interpretation and reporting. Data sources: Systematic review searching; MEDLINE, EMBASE, PsycINFO, CINAHL from January 1990 to 1st August 2022. Results: About 64 publications from 54 studies were synthesised (from 9259 retrieved). Two main themes were identified: (1) importance of being known to a service and (2) high-quality coordination of care. A typology of out-of-hours service provision was constructed using three overarching dimensions (service times, focus of team delivering the care and type of care delivered) resulting in 15 categories of care. Only nine papers were randomised control trials or controlled cohorts reporting outcomes. Evidence on effectiveness was apparent for providing 24/7 specialist palliative care with both hands-on clinical care and advisory care. Only nine publications reported economic evaluation. Conclusions: The typological framework allows models of out-of-hours care to be systematically defined and compared. We highlight the models of out-of-hours care which are linked with improvement of patient outcomes. There is a need for effectiveness and cost effectiveness studies which define and categorise out-of-hours care to allow thorough evaluation of services.